The Acehnese Numerals in the Aceh Jaya District - Irnanda, Septhia; Muliawati, Ida; Yulsafli, Yulsafli; Muthalib, Kismullah Abdul; Inayah, Nurul (PAROLE: Journal of Linguistics and Education, 2024)
This study examines the phonological varieties of Acehnese numeral words, using primary data from ten villages in the Aceh Jaya district on the west coast of Aceh, Indonesia, and supplementing it with secondary data from Standard Acehnese, Proto-Chamic, and other relevant languages and proto-languages. The research aims to elucidate the historical relationship between the Acehnese and Chamic languages through a comparative analysis. Fifteen numeral words (one to ten, eleven, twelve, twenty, one hundred, and one thousand) were elicited from informants aged 40 to 65. The collected data were recorded, transcribed into IPA symbols, and subsequently analysed. The findings indicate that the split between the Acehnese-Chamic branch and the Malayic languages occurred during the period when the terms for 'eight' and 'nine' were still undergoing lexical stabilisation. The Acehnese language was then subgrouped from Chamic, initially as a dialect. A few centuries later, the ancestors of the Acehnese migrated from mainland Southeast Asia to Sumatra, where their numeral system was subsequently influenced by borrowing from the Malay language. The dialects spoken on the west coast of Aceh retain linguistic evidence of the presence of a language similar to Proto-Chamic and its early contact with indigenous Sumatran populations, and those from the Malay Peninsula.